B-cell–driven relapse and anti-CD20 rescue therapy after Alemtuzumab in RRMS: case report and literature review - Bruno, Pietro Antonio; Barone, Stefania; Pascarella, Angelo; Lanza, Pier Luigi; Tinelli, Emanuele; Gambardella, Antonio; Valentino, Paola (Frontiers in Immunology, 2026)
BackgroundAlemtuzumab is an immune reconstitution therapy (IRT) approved for highly active relapsing–remitting multiple sclerosis (RRMS). Notably, the differential reconstitution of B and T cells after alemtuzumab may trigger paradoxical B–cell–mediated inflammation and secondary autoimmunity.Case ReportWe describe the case of a 44-year-old woman with RRMS who experienced a severe, steroid-resistant relapse nine months after her second alemtuzumab cycle. Lymphocyte subtyping revealed disproportionate B-cell repopulation, suggesting a B-cell–mediated immunopathogenesis. Early ocrelizumab switch resulted in rapid clinical and radiological recovery and sustained stability.Literature reviewWe conducted a narrative review of early and paradoxical disease reactivation after alemtuzumab, identifying common features: early onset, poor steroid response, large or tumefactive lesions, and marked B-cell hyperrepopulation. Anti-CD20 therapy often induced rapid remission. These findings may suggest a distinct B-cell–driven mechanism of inflammation. Prior exposure to fingolimod has been observed in several cases, but does not uniformly account for the observed phenotype.ConclusionThis case contributes to the growing evidence that a subset of patients may experience B-cell–driven inflammatory reactivation after alemtuzumab treatment. Lymphocyte subtyping should be performed, and a predominance of CD19+ B cells can guide a timely therapeutic switch to anti-CD20 therapy. Further studies are needed to define whether this represents a distinct post-IRT immunopathological entity.